New ganoderma lucidum strain and ganoderma lucidum tablet containing same
By using the synergistic effect of specific Ganoderma lucidum strain ZL-288 and auxiliary materials, the problem of insurmountable bitterness in Ganoderma lucidum tablets is solved, and Ganoderma lucidum tablets with high quality and antioxidant functions are prepared, which has enhanced the proportion and development potential of Ganoderma lucidum in the preparation.
Patent Information
- Application Number
- CN202311241214.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
The bitter taste in existing Ganoderma lucidum tablets is difficult to overcome, and the proportion of Ganoderma lucidum in the preparation is small, which affects the further development of the preparation.
A specific Ganoderma lucidum strain ZL-288 (CGMCC NO.40776) was used to screen high-quality Ganoderma lucidum raw materials by detecting its appearance characteristics, internal quality and texture analysis, and combined with auxiliary materials such as dextrin, magnesium stearate and aspartame to prepare Ganoderma lucidum tablets with antioxidant functions.
The prepared Ganoderma lucidum tablets have good chewability, uniform color, suitable sweet and sour in the mouth, no bitter taste, moderate hardness, and have strong scavenging ability for DPPH free radicals and superoxide anion free radicals, which significantly improves the antioxidant function of Ganoderma lucidum tablets.
Smart Images

Figure CN119685169A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a new strain of ganoderma lucidum and a ganoderma lucidum tablet containing the new strain. Background Art
[0002] Ganoderma lucidum is a precious traditional Chinese medicine. In terms of systematic classification, it belongs to the Myceteae, Basidiomycota, Hymenomycetes, Ganodermatales, Ganodermataceae. Its scientific name is G. lucidum karst. Studies have shown that Ganoderma lucidum has strong pharmacological activity and has a good regulating effect on the human immune system, nervous system and cardiovascular system. It has extremely high nutritional and medicinal value. Its main functional ingredients are Ganoderma polysaccharides, triterpenoids, protein amino acids, sterol compounds, etc., mainly including the dried fruiting bodies of Ganoderma lucidum (Leyss. exFr.) Karst. and G. sinense. The authentic Ganoderma lucidum was included in the Pharmacopoeia of the People's Republic of China in 2000. Wild Ganoderma lucidum is mainly distributed in my country's tropical and subtropical broad-leaved forest areas and Panzhihua area of Sichuan Tibetan area. my country is the country with the richest known species and quantity of Ganodermaaceae fungi, and it is mainly concentrated in the mountainous areas of Northeast China, Zhejiang, Fujian, Anhui and southwestern Shandong.
[0003] Since Ganoderma lucidum contains bitter substances, Tsuyoshi et al. extracted triterpenoids from Ganoderma lucidum, graded their bitterness by sensory evaluation, and determined the triterpenoid structure by spectroscopy, and then studied the bitterness. Jiang-Jing GAO et al. established a high-performance liquid chromatography to quantitatively analyze the triterpenoid components in Ganoderma lucidum products. The results showed that there were significant differences in the content and composition of triterpenoids in samples of different strains, while the relative proportions of alcohols and acids were not significantly different. Studies have shown that triterpenoid compounds in Ganoderma lucidum fruiting bodies are the main substances that affect its bitterness.
[0004] In order to overcome the bitterness of Ganoderma lucidum, there are literature reports that Ganoderma lucidum raw materials are made into tablets, such as: CN201611205994.6, invention name: A Ganoderma lucidum tablet and a method for preparing Ganoderma lucidum tablets, which include main ingredients and auxiliary materials. In terms of weight, the main ingredients include 6-9 parts of Ganoderma lucidum polysaccharides, 1-2 parts of Ophiopogon japonicus polysaccharides, 3-4.5 parts of Lilium polysaccharides, 1.5-2.5 parts of Anemarrhena asphodeloides polysaccharides and 1-2 parts of Ganoderma lucidum triterpenes. The auxiliary materials include 6-21 parts of fillers, 0.04-0.5 parts of lubricants, 2-20 parts of wetting agents and 1-5 parts of adhesives. Through the synergistic effect between Ganoderma lucidum polysaccharides, Ophiopogon japonicus polysaccharides, Lilium polysaccharides, Anemarrhena asphodeloides polysaccharides and Ganoderma lucidum triterpenes, hydroxyl radicals, DPPH radicals and ABTS radicals can be effectively scavenged to prevent oxidation and aging. CN201710013050.7, Invention Name: A Ganoderma lucidum tablet and its preparation method, the present invention discloses a Ganoderma lucidum tablet and its preparation method, the composition of the Ganoderma lucidum tablet is 50-550 parts of Ganoderma lucidum alcohol extract powder, 50-550 parts of Ganoderma lucidum water extract powder, 200 parts of Ganoderma lucidum fruiting body powder, 200 parts of broken wall Ganoderma lucidum spore powder. In the process of preparing Ganoderma lucidum alcohol extract powder and water extract powder, Ganoderma lucidum fruiting body powder is used to replace the conventional filling disintegration and lubricant auxiliary materials. The literature mainly uses Ganoderma lucidum extract or Ganoderma lucidum fruiting body powder. There are also reports that the polysaccharides in Ganoderma lucidum are prepared into tablet candies, such as: Application number: CN202111205538.2, Invention Name: Mushroom and Ganoderma lucidum polysaccharide composite tablet candy for improving immunity and its preparation method, specifically discloses a mushroom and Ganoderma lucidum polysaccharide composite tablet candy for improving immunity and its preparation method. The composite tablet candy of shiitake mushroom and ganoderma lucidum polysaccharide is made of the following raw materials in weight percentage: 8-30% shiitake mushroom polysaccharide, 3-10% ganoderma lucidum polysaccharide, 8-15% beta-glucan, 0-15% yeast extract, 0-15% zinc gluconate, 10-25% trehalose, 0-50% sustained-release composition, 0-0.3% edible pigment, 0-0.3% edible flavor, and the balance is supplemented to 100% by other auxiliary materials suitable for composite tablet candy. The present application has the effects of improving the body's immunity, promoting gastrointestinal absorption and enhancing metabolism through the compounding of shiitake mushroom polysaccharide and ganoderma lucidum polysaccharide and other ingredients. Application number: CN202110283509.1, invention name: A Ganoderma lucidum coffee tea tablet candy and a preparation method thereof, discloses a Ganoderma lucidum coffee tea tablet candy and a preparation method thereof, and the raw material components include 1-10 parts of sugar-free complex sugar or sucrose, 5-95 parts of coffee, 5-95 parts of milk powder, 5-95 parts of Ganoderma lucidum powder, 5-60 parts of tea extract, 1-5 parts of Cordyceps militaris extract, 1-8 parts of Hericium erinaceus extract, 1-4 parts of Chaga extract, 1-1.5 parts of Rhodiola rosea extract, 1-1.5 parts of rose hip extract, 2-5 parts of low-substituted carboxypropyl cellulose, 3-20 parts of sodium bicarbonate and 0.2-0.5 parts of magnesium stearate.After the raw material components are screened, the raw materials are crushed, sieved, weighed, mixed, made into soft materials, granulated, granulated, tableted, inspected, and packaged to obtain the product. Application number: CN202310710467.4, invention name: A Ganoderma lucidum tablet candy and its production process. The present invention relates to the field of tablet candy technology, in particular to a Ganoderma lucidum tablet candy and its production process, the ingredients of which include the following: 36% Ganoderma lucidum composite powder, 30% processing aid, 20% microcrystalline cellulose, 10% sweetener, 3% white sugar, and 1% anti-caking agent. The processing aid also includes sorbitol and maltodextrin, and the proportions of sorbitol and maltodextrin in the total ingredients are respectively 25% and 5%, the anticaking agent is magnesium stearate, the sweetener is lactose, the wet granulation process of Ganoderma lucidum tablet candy, sieving premixing, Ganoderma lucidum composite powder through a 100-mesh sieve, lactose, microcrystalline cellulose, maltodextrin, 2% of the total amount of white sugar through a 40-mesh sieve, after sieving, put them into a trough mixer together, dry mix for more than 3 minutes, prepare the adhesive, prepare the remaining 1% of the total amount of white sugar and purified water at a mass ratio of 1:9 to prepare the adhesive, and spray the adhesive into the material in step 1 in the trough mixer. The bitterness of the Ganoderma lucidum composite powder used in this patent is still the main problem that is difficult to overcome, and the proportion of Ganoderma lucidum in the preparation is small, which affects the further development of the preparation. Summary of the invention
[0005] The invention provides a ganoderma lucidum which is suitable for the raw material of ganoderma lucidum slices. The invention also provides ganoderma lucidum slices containing the new strain.
[0006] The present invention provides a Ganoderma lucidum, which is a Ganoderma lucidum with a deposit number of CGMCC NO.40776 deposited in the General Microbiological Center of China Microorganism Culture Collection Committee (No. 3, Yard No. 1, Beichen West Road, Chaoyang District, Beijing), a deposit date of August 3, 2023, and a deposit classification name of Ganoderma lucidum.
[0007] The average radius of the Ganoderma lucidum is 77.95 cm, and the average thickness is 15.88 cm.
[0008] The hardness of the Ganoderma lucidum is 1133.76±64.2 gf, adhesion is 0.95±0.01 gf, resilience is 0.36±0.02 gf, elasticity is 0.98±0.01 gf, chewiness is 1060.95±70.8 gf, and bitterness is 0.88±0.13.
[0009] The present invention provides the use of the ganoderma lucidum in preparing a health food or medicine with antioxidant function, wherein the preparation of the health food or medicine is an oral preparation, and further, the oral preparation is a tablet.
[0010] The invention provides a food containing the ganoderma lucidum.
[0011] The invention provides a ganoderma lucidum tablet containing the ganoderma lucidum.
[0012] The ganoderma lucidum tablets are prepared from the following raw materials and auxiliary materials in percentage by weight:
[0013] Ganoderma lucidum 50%-80%, filler 30%-50%, lubricant 1%-5%, flavoring agent 0.6%-1.4%; the filler is one or a mixture of two or more of microcrystalline cellulose, lactose, starch, and dextrin;
[0014] The lubricant is one or a mixture of two or more of magnesium stearate, talcum powder, and micro-powder silica gel;
[0015] The flavor corrector is: one or a mixture of two or more of aspartame or stevioside.
[0016] The ganoderma lucidum is raw powder and is sieved through a 100-200 mesh sieve.
[0017] More preferably, it is prepared from the following raw materials in percentage by weight:
[0018] Ganoderma lucidum 59.84%, dextrin powder 36.20%, magnesium stearate 3.13%, aspartame 0.83%;
[0019] The ganoderma lucidum is raw medicinal powder and is sieved through a 120-mesh sieve.
[0020] The ganoderma lucidum raw material used in the ganoderma lucidum slices of the present invention is obtained by screening after evaluating the fruiting bodies of different ganoderma lucidum strains based on texture as an index, and the raw material quality is reliable. The ganoderma lucidum slices prepared by the raw material have good chewing properties, uniform color, smooth surface, appropriate sweet and sour taste, no bitterness, and moderate hardness. The raw material has strong scavenging ability for DPPH free radicals and superoxide anion free radicals, and has significant antioxidant function. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Response surface and contour lines of the interactive effect of dextrin and magnesium stearate addition on comprehensive score
[0022] Figure 2 Response surface and contour lines of the interactive effect of dextrin and aspartame addition on comprehensive score
[0023] Figure 3 Response surface and contour lines of the interactive effect of microcrystalline cellulose addition and magnesium stearate addition on comprehensive score
[0024] Figure 4 Comparison of different Ganoderma lucidum slices DETAILED DESCRIPTION
[0025] Example 1 Ganoderma lucidum strains of the present invention
[0026] The Ganoderma lucidum strain ZL-288 of the present invention (the deposit number is CGMCC NO.40776, the deposit date is August 3, 2023, the deposit classification name is Ganoderma lucidum, and the deposit unit is General Microbiology Center of China Microorganism Culture Collection Administration Committee) is examined for its appearance characteristics, the content of its internal substances is determined, and a texture analyzer is used to perform a full texture analysis and sensory evaluation on it, as well as analyze the correlation between various texture data parameters and sensory scores, principal component analysis is used to determine the weight of each parameter, and its quality is comprehensively evaluated.
[0027] The main features are as follows:
[0028] 1. Appearance;
[0029] Table 1 Appearance properties test results
[0030]
[0031] 2. Sample size:
[0032] The results of the sample radius and thickness are shown in the table.
[0033] Table 2 Sample radius and thickness measurement results
[0034]
[0035] 3. Production cycle: 120 days
[0036] Example 2 Intrinsic quality detection of the Ganoderma lucidum strains of the present invention
[0037] 1. Detection of polysaccharide content
[0038] 1.1 Polysaccharide extraction method
[0039] Weigh 2.0g of sample powder, place in a round-bottom flask, add 60ml of water, let stand for 1 hour, heat and reflux for 4h, filter while hot, rinse the filter and filter residue with a small amount of hot water several times, place the filter residue and filter paper in a round-bottom flask, add 60ml of water, heat and reflux for 3h, repeat the first filtration step, combine the filtrate, put it in a water bath to evaporate, dissolve the residue with a small amount of hot water, slowly add 75ml of anhydrous ethanol while stirring, shake well, precipitate at 4℃ for more than 12h, adjust the centrifuge at 4℃, 10000r / min, centrifuge for 15min, discard the supernatant, dissolve the precipitate with hot water and make up to volume in a 50ml volumetric flask, cool, take an appropriate amount of solution, and continue centrifugation with the above parameters. Take 1ml and dilute 10 times, shake well for use.
[0040] 1.2 Determination of polysaccharides
[0041] Take some anhydrous glucose, place it in an oven at 105℃ until constant weight, prepare 0.12mg / ml anhydrous glucose solution as a reference, take 0.1, 0.2, 0.3, 0.4, 0.5, 0.6ml of the reference sample solution, place them in 5ml test tubes respectively, add water to 1ml, quickly add 3ml of anthrone sulfate solution (accurately weigh 0.05g of anthrone, add 50ml of sulfuric acid to dissolve it, shake well), shake well immediately, place it for 15min to react, immediately place it in an ice water bath for 15min to stop the reaction, take it out, use water plus anthrone sulfate solution as the blank group, select a wavelength of 625nm in the UV-Visible wind photometer to measure its absorbance value, use absorbance as the ordinate and concentration as the abscissa, and draw a standard curve. Take 1ml of the test sample and add 3ml of anthrone sulfate solution to the control group, read the content of anhydrous glucose in the test sample solution from the standard curve and calculate it.
[0042] 2. Detection of triterpene content in samples
[0043] 2.1 Extraction method of triterpenes
[0044] Weigh 2.0 g of sample powder, place it in a stoppered conical flask, add 50 ml of anhydrous ethanol, ultrasonically treat (power 100 W, frequency 45 kHz) for 45 min, filter, place the filtrate in a 100 ml volumetric flask, rinse the filter and filter residue with anhydrous ethanol, make up the volume, and shake well.
[0045] 2.2 Determination of triterpenes
[0046] Take an appropriate amount of oleanolic acid, accurately weigh it, and use methanol to prepare a solution with a concentration of 0.2 mg / ml as a reference substance. Take 0.1, 0.2, 0.3, 0.4, and 0.5 ml of the reference sample solution, respectively, and place them in 15 ml test tubes. After cooling, evaporate to dryness, quickly add 0.2 ml of the newly prepared vanillin acetic acid solution (vanillin 1.0 g, acetic acid 20 ml, dissolve and mix well) and 0.8 ml of perchloric acid, shake well, react in 70 ° C water for 15 min, then immediately place in an ice water bath for 5 min to stop the reaction, take out and add 4 ml of ethyl acetate solution, shake well, use water plus vanillin acetic acid solution and perchloric acid solution as blank groups, select a wavelength of 545 nm in a UV-visible spectrophotometer to determine the absorbance, and draw a standard curve with absorbance as the ordinate and concentration as the abscissa. Take 0.2 ml of the test sample and add 0.2 ml of vanillin glacial acetic acid solution and 0.8 ml of perchloric acid solution to the control group. Read the content of oleanolic acid in the sample from the standard curve and calculate it.
[0047] 3. Full texture determination method
[0048] The collected Ganoderma samples were subjected to TPA test using a texture analyzer (TA.XT plus, Stable Micro Systems, UK). A 1×1 cm square was cut from the middle of the Ganoderma fruiting body and subjected to TPA test using a P / 36R probe. The hardness, elasticity, chewiness, adhesion, resilience and other parameters of the sample were obtained from the texture characteristic curve.
[0049] Hardness is the maximum force peak of the first compression cycle, which means that after Ganoderma lucidum exceeds the biological yield point, the external environment continues to exert a certain degree of pressure. The magnitude of the force on Ganoderma lucidum reflects the nature of Ganoderma lucidum's resistance to deformation.
[0050] Adhesion is the negative peak area of the first extrusion and is the work done by the probe to detach from the Ganoderma lucidum surface.
[0051] Resilience refers to the level to which sweet potato tubers can deform before breaking. It is a measure of internal cohesive strength and reflects the strength of the internal bonding force of the tuber and its ability to maintain integrity.
[0052] Elasticity refers to the height of the sample that recovers after the first squeezing of Ganoderma lucidum and before the second squeezing begins.
[0053] Chewability reflects Ganoderma lucidum's sustained resistance to chewing. It is the product of hardness, elasticity and cohesion, and comprehensively reflects its sustained resistance to chewing.
[0054] Resilience refers to the ratio of the area before the deformation target to the area after the deformation target during the first pressure.
[0055] Test parameters: speed before test: 1.00mm / s, test speed 1.00mm / s, speed after test 1.00mm / s, trigger force 10g, target mode: deformation 5%, interval between two presses 1s, each sample was measured 3 times and the average value was taken.
[0056] 4. Bitterness Determination Sample Preparation
[0057] After ZL-288 Ganoderma lucidum was powdered, it was passed through a 60-mesh sieve for later use. 2.00 g of sample was selected, 20 times of water was added, and it was boiled in water for 10 min. The sample was filtered through a 40 μm pore size filter. The residue was boiled in water for 10 min (Ganoderma lucidum: water = 1:20), and then filtered through a 40 μm pore size filter. The two Ganoderma lucidum extracts were combined for bitterness evaluation.
[0058] 5 Sensory evaluation of bitterness
[0059] The sensory evaluation experimental team is composed of 10 technical personnel from the food industry. All reviewers need to have certain professional knowledge, good sensory acuity, and basic sensory evaluation knowledge and skills. Before the evaluation, the reviewers will be trained. During the evaluation, the reviewers are required to evaluate objectively without any personal preferences or aversions. Rinse your mouth with pure water before the sensory evaluation. During the evaluation, take the test solution in a disposable cup and hold it in your mouth for 15 to 30 seconds. Move your mouth so that the test solution fully contacts the entire tongue. Carefully identify the taste, then spit out the test solution. Rinse the bitterness according to the table below, and the average of the group members' scores is the final score. After carefully tasting the test solution each time, rinse your mouth with pure water until there is no bitterness in your mouth, and wait for 1 minute before tasting the next test solution. The reference standard is shown in Table 3.
[0060] Table 3 Bitterness Standard of Ganoderma Lucidum
[0061]
[0062] 6 Data processing
[0063] The test data are expressed as mean ± standard deviation, and the mean is the average of 3 replicates of each sample. IBM.SPSS26.0 was used to perform correlation analysis and principal component analysis on the texture parameters.
[0064] 7 Results and Analysis
[0065] 7.1 Test results of polysaccharide content of samples
[0066] The standard curve of anhydrous glucose is Y = 12.322X-0.0074, R 2 =0.9928. The test results of polysaccharide content of the samples are shown in the table.
[0067] Table 4 Examination of the linear relationship of anhydrous glucose
[0068]
[0069]
[0070] Table 5 Polysaccharide content detection results
[0071]
[0072] 7.2 Test results of triterpenoid content of samples
[0073] The standard curve of oleanolic acid is Y=199.42X+4.7657, R 2 =0.9911. The triterpene test results of the samples are shown in the table.
[0074] Table 6 Examination of the linear relationship of oleanolic acid
[0075]
[0076] Table 7 Triterpenoid detection results
[0077]
[0078] 7.3 Sample texture data measurement results
[0079] The results of the full texture data of the samples are shown in the table
[0080] Table 8 Ganoderma lucidum texture data
[0081]
[0082] 7.4 Sample Bitterness Test Results
[0083] Table 9 Bitterness test results of samples
[0084]
[0085] The bitterness value is the result obtained from sensory evaluation, has no unit, and is expressed as a percentage. The bitterness value is expressed by the content of triterpenes and sterols in Ganoderma lucidum, and is calculated as a mass percentage.
[0086] Example 3 Preparation of Ganoderma Lucidum Tablets of the Present Invention
[0087] Formula: 36.20% dextrin powder, 3.13% magnesium stearate, 0.83% aspartame, and 59.84% Ganoderma lucidum.
[0088] Preparation process: Chinese herbal medicine Ganoderma lucidum → drying → ultrafine grinding → auxiliary material preparation → weighing → mixing → tableting → packaging
[0089] Raw materials: Take Lingzhi strain, clean
[0090] Drying and crushing: Ganoderma lucidum is dried in an oven at 60°C until it reaches a constant weight, then crushed into ultrafine powder for later use.
[0091] Preparation of auxiliary materials: prepare additives such as dextrin, magnesium stearate, and aspartame.
[0092] Weighing: Based on 6g of each candy, weigh 3.59g of Ganoderma lucidum, 2.17g of dextrin, 0.19g of magnesium stearate, and 0.05g of aspartame.
[0093] Mixing: Use a blender at a speed of 10,000 to 20,000 r / min to mix the Ganoderma lucidum powder with dextrin, magnesium stearate and aspartame in sequence until the color of the mixed powder is uniform when observed with the naked eye.
[0094] Tableting: Place equal amounts of the mixed powder into a tableting mold and use a single-punch tablet press for tableting.
[0095] Example 4: Screening test of the ganoderma lucidum tablets of the present invention
[0096] 1. Determination of raw material mesh size
[0097] 1.1 Determination of the angle of repose
[0098] (2) The Ganoderma lucidum strains were subjected to single crushing treatment, and 100 mesh, 120 mesh, and 200 mesh were selected for sieving and used for later use.
[0099] Place the funnel on the drawing paper at a certain distance, add the material particles into the funnel, and let the material particles flow freely from the bottom of the funnel until the material leaking out forms a cone. The diameter of the cone is 2R, the height is H, and the angle of repose is the angle between the inclined surface of the cone and the horizontal plane, tanθ=H / R, and the angle of repose θ is obtained.
[0100] 1.2 Optimization of the ratio of raw materials and auxiliary materials
[0101] 1.2.1 Single Factor Experiment
[0102] 1.2.1.1 Selection of filler types and dosage
[0103] Common fillers used in tablets include microcrystalline cellulose, lactose, starch, dextrin, etc. For the direct powder tableting process, the most suitable filler has good material fluidity, compressibility and adhesion. This test uses material fluidity, tablet appearance, hardness and friability as the evaluation indicators to screen the commonly used single fillers. The specific formula is shown in Table 10.
[0104] Table 10 Filler types and their proportions
[0105]
[0106] 1.2.1.2 Selection of lubricant type and amount
[0107] Lubricants are one of the indispensable auxiliary materials in tablet preparation. The action mechanisms of lubricants include the following: 1. Improvement of electrostatic distribution on the surface of particles; Improvement of particle surface roughness; Selective adsorption of gas; Weakening of van der Waals forces between particles; Adherence to the surface of particles to reduce friction, etc. The main lubricants include magnesium stearate, talcum powder, micro-powder silica gel, etc. The test indicators are the same as fillers. The specific formula is shown in Table 11.
[0108] Table 11 Lubricant types and their formulations
[0109]
[0110]
[0111] 1.2.1.3 Selection of flavoring agent type and dosage
[0112] Flavor correctors can effectively improve the taste of tablets and increase their flavor. They mainly include aspartame, stevioside, sucrose, rock sugar powder, etc. By consulting the literature and the formulas of commercially available products, the formula for this test was selected (see Table 12).
[0113] Table 12 Flavoring agent types and their formulations
[0114]
[0115] 1.2.2 Response surface optimization experiment
[0116] A total of three factors, namely, the addition amount of dextrin, magnesium stearate, and aspartame, were selected. Based on the single factor experiment, a response surface test was conducted according to the Box-Behnken experimental design principle to obtain the optimized tableting formula parameters. The factors and levels of the response surface test are shown in Table 13.
[0117] Table 13 Factors and levels of response surface experiment
[0118]
[0119] 1.2.3 Sensory evaluation
[0120] A sensory evaluation panel of 10 people was randomly selected to taste the Lingzhi tablets. The Lingzhi tablets were placed under natural light to observe their appearance; the taste and flavor of the tablets were experienced after rinsing the mouth with boiled water, and the scores were given according to Table 14. The author will take the average of the ten groups of data as the final sensory evaluation score.
[0121] Table 14 Sensory Rating Table
[0122]
[0123]
[0124] 1.2.4 Determination of tablet weight differences
[0125] Select 10 intact samples, weigh them to get the average, weigh each piece separately, and compare it with the average weight. The weight difference limit for the sample average weight of more than 0.3g is ±5.0%. Note that no more than 2 pieces should exceed the weight difference limit, and no piece should exceed the limit by 1 times.
[0126] 1.2.5 Hardness test
[0127] At room temperature, the hardness of the chewable tablets was measured using a texture analyzer with the following parameters set: compression mode, speed before test: 1.0 mm / s; speed during test: 2.0 mm / s; speed after test: 10.0 mm / s; target mode: 2 mm; trigger force: 20 g. Each group of samples was measured 7 times in parallel, and the minimum and maximum values were removed to obtain the average value.
[0128] 1.2.6 Friability test
[0129] The friability tester is adjusted to 25 revolutions per minute, and the test time is set to 4 minutes. Each time, 6.5g of the total weight of the test sample is taken, placed in a weighing bottle for weighing, and then placed in a cylinder and rotated 100 times. The test piece shall not be broken, cracked or crushed.
[0130] 1.2.7 Multi-index comprehensive scoring method
[0131] The comprehensive score (Q) of the four indicators of tablet weight difference (a), hardness (b), friability (c) and sensory score (d) was used as the optimization index of the response surface experiment. The weight of the chewable tablet is greater than 0.3g, and the friability should be less than 2%. The smaller a and c are, the better; for easy chewing and better taste, the hardness should be controlled between 70 and 120N, and the larger b is, the better. According to the index control requirements and their contribution to formability, a dimensionless comprehensive score is performed. The specific content of the multi-index comprehensive scoring method is shown in Table 15. The comprehensive score is the sum of the values of each index, that is, Q = a + b + c + d.
[0132] Table 15 Multi-index comprehensive scoring method
[0133]
[0134] 1.2.8 Determination of antioxidant capacity
[0135] After grinding the prepared samples, weigh 0.10, 0.20, 0.30, 0.40, 0.50, and 0.60 g of samples into 5 mL of distilled water, and prepare the sample mass concentrations to be 0.02, 0.04, 0.06, 0.08, 0.10, and 0.12 g / mL, respectively. After incubating in a water bath at 85°C for 2 h, centrifuge at 5000 r / min for 8 min to obtain the extract, which was used to determine the antioxidant activity. The experiment was repeated twice.
[0136] 1.2.8.1 Determination of DPPH free radical scavenging ability
[0137] The above sample extracts were added to 2 mL of 0.1 mmol / L DPPH solution, mixed thoroughly, and then protected from light for 30 min. VC was selected as the positive control, and the absorbance value A was measured at a wavelength of 517 nm. Ultrapure water was used instead of the sample as a blank control to measure the absorbance A0, and anhydrous ethanol was used instead of the DPPH reaction solution to measure the absorbance A1.
[0138] DPPH free radical scavenging rate / % = (1-(A-A1)÷A0)×100
[0139] 1.2.8.2 Determination of superoxide anion free radical scavenging ability
[0140] Add 3 ml of 50 mmol / L Tris-HCl (PH=8.2) buffer solution to the sample extract and react at 30°C for 20 min. Cool to room temperature, add 0.4 ml of 25 mmol / L pyrogallol solution, mix thoroughly, react for 5 min in a 25°C water bath, and add 1 ml of 10 mol / L hydrochloric acid to terminate the reaction. Select VC as the positive control and measure the absorbance value A at a wavelength of 320 nm. Replace the sample with ultrapure water as a blank control and measure the absorbance A0. Replace pyrogallol and hydrochloric acid with ultrapure water and measure the absorbance A1.
[0141] Superoxide anion free radical scavenging rate / % = (1-(A-A1)÷A0)×100
[0142] 1.2.8.3 Determination of hydroxyl radical scavenging ability
[0143] Add 1 ml of 6.0 mmol / L FeSO4 solution, 1 ml of 6.0 mmol / L salicylic acid ethanol solution and 1 ml of 8.8 mmol / L hydrogen peroxide solution to the above sample extracts, shake them thoroughly, and react in the dark at 37°C for 20 min. Measure the absorbance A at a wavelength of 510 nm. Use distilled water instead of the sample as a blank control to measure the absorbance A0. Use distilled water instead of the hydrogen peroxide reference to measure the absorbance A1.
[0144] Hydroxyl free radical scavenging rate / % = (1-(A-A1)÷A0)×100
[0145] 1.3 Data Analysis
[0146] Each experiment was repeated three times. Origin8.0 software was used for drawing and Design-Expert13 software was used for Box-Behnken experimental design.
[0147] 2 Results and analysis
[0148] 2.1 Determination of raw material mesh size
[0149] The size of the material's repose angle represents the quality of the material's fluidity. The essential factor for successful tableting is that the material has good fluidity. Good fluidity allows the particles to be fully mixed and flow smoothly into the punch. The weight difference of the pressed tablets is small, and the difference in the effective ingredients in the tablets is also small. Good fluidity can reduce the friction between the material and the punch, reduce damage to the equipment, facilitate the push-out and sliding of the tablets, and make the tablet surface smooth and lubricated with excellent appearance. The repose angle standard is shown in Table 16.
[0150] Table 16 Repose angle standards
[0151]
[0152]
[0153] Table 17 Repose angle measurement results
[0154]
[0155] 2.2 Single Factor Experiment
[0156] 2.2.1 Filler selection results
[0157] According to the indicators of whether the tablet is formed and whether the tablet hardness is met, the appropriate filler is selected. It can be seen from the table that when the addition amount is higher than 30%, the hardness meets the quality requirements of the tablet. Further refinement shows that, as shown in Table 18, the amount of filler added has a greater impact on the appearance and flavor of the Ganoderma lucidum tablets, and the impact on the taste is not obvious within the range. With the increase in the proportion of the added amount, the appearance of the Ganoderma lucidum tablets tends to rise first and then fall, the taste has no significant difference at first and then falls, and the bitterness gradually disappears. If the filler is added too little, it cannot play a corresponding filling and bonding role on the Ganoderma lucidum fine powder, and the compressibility of the tablet is low; if the filler is added too much, the taste is heavy, there is a feeling of discomfort in the mouth, and the acceptance is not high. The standard hardness of the product's tablets and the difference in tablet weight are both developing in a positive trend, while the changes in friability are not very regular. A higher friability will make the tablets taste rough and powdery. When the amount of filler added is higher than 40%, the change in hardness is very gentle. On the premise of maximizing the amount of Ganoderma lucidum added, microcrystalline cellulose, lactose and dextrin with addition amounts of 30% and 35% were selected for the next screening.
[0158] Table 18 Filler selection results
[0159]
[0160]
[0161] Table 19 Further screening results of fillers
[0162]
[0163] Table 20 Further screening results of fillers
[0164]
[0165]
[0166] Table 21 Further screening results of fillers
[0167]
[0168] 4.2.2 Lubricant selection results
[0169] 4.2.2.1 Changes in tablet quality of selected lubricants when the filler is 30% microcrystalline cellulose
[0170] With 65% ganoderma lucidum added and 30% filler added, the change in tablet quality when the lubricant was 1% to 5% was investigated.
[0171] Table 22 Changes in the quality of lubricant tablets when the filler is microcrystalline cellulose
[0172]
[0173]
[0174] 4.2.2.2 Changes in tablet quality of selected lubricants when filler is 30% lactose
[0175] The change of tablet quality when the lubricant content was 1% to 5% was investigated by adding 65% Ganoderma lucidum and 30% filler.
[0176] Table 23 Changes in the quality of lubricant tablets when the filler is lactose
[0177]
[0178] 4.2.2.3 Changes in tablet quality of selected lubricants when the filler is 30% dextrin
[0179] The change of tablet quality when the lubricant content was 1% to 5% was investigated by adding 65% Ganoderma lucidum and 30% filler.
[0180] Table 24 Changes in the quality of lubricant tablets when the filler is dextrin
[0181]
[0182] 4.2.2.4 Changes in tablet quality of selected lubricants when the filler is 35% microcrystalline cellulose lactose
[0183] 60% ganoderma lucidum, 35% filler, and 1% to 5% lubricant to investigate the quality change of the tablets
[0184] Table 25 Changes in the quality of lubricant tablets when the filler is microcrystalline cellulose
[0185]
[0186]
[0187] 4.2.2.5 Changes in tablet quality of selected lubricants when the filler is 35% lactose
[0188] 60% ganoderma lucidum, 35% filler, and 1% to 5% lubricant to investigate the quality change of the tablets
[0189] Table 26 Changes in the quality of lubricant tablets when the filler is lactose
[0190]
[0191] 4.2.2.6 Changes in tablet quality of selected lubricants when the filler is 35% dextrin
[0192] The change of tablet quality when the lubricant content was 1% to 5% was investigated by adding 60% Ganoderma lucidum and 35% filler.
[0193] Table 27 Changes in the quality of lubricant tablets when the filler is dextrin
[0194]
[0195] 4.2.2.7 Effect of magnesium stearate addition on the quality of Ganoderma lucidum tablets
[0196] Table 28 Effect of magnesium stearate addition on the quality of Ganoderma lucidum tablets
[0197]
[0198]
[0199] It can be seen from the table that with the addition of lubricants, the friability of the Ganoderma lucidum tablets is gradually improving, because the lubricant can improve the fluidity between powders. When the addition amount of filler is 30%, all lubricants used cannot reduce the friability to below 2.5%, so the addition of 30% filler is not feasible, and the hardness is too low. When the addition amount of filler is 35%, magnesium stearate has the best friability when combined with any type of filler, so magnesium stearate is selected as the lubricant for this Ganoderma lucidum tablet. And when the same lubricant is combined with different types of fillers, it can be seen that dextrin is the best performing filler in this experiment. Further combined with the graph and table, as the amount of magnesium stearate added increases, the gloss of the Ganoderma lucidum tablets becomes more uniform, the shape is complete and the texture is firm. However, if the amount of magnesium stearate added is too high, the softening degree of the tablets will be deepened. At the same time, magnesium stearate itself has a dry taste, which will reduce the taste of the Ganoderma lucidum tablets. Therefore, considering all factors, the best combination is 35% dextrin plus 4% magnesium stearate.
[0200] 4.2.2.8 Flavoring agent selection results
[0201] The sensory changes of Ganoderma lucidum tablets with flavoring agents ranging from 0.6 to 1.4% were examined with 35% dextrin and 4% magnesium stearate.
[0202] Table 29 Selection results of flavor correctors
[0203]
[0204]
[0205] It can be seen from the table that the addition of flavoring agents has no significant effect on the weight difference, hardness and brittleness of Ganoderma lucidum tablets. In addition, with the increase in the amount of flavoring agents added, the greatest impact is on its flavor. Based on various aspects such as health conditions, the better aspartame was comprehensively selected as the flavoring agent for this Ganoderma lucidum tablet, and the addition amount of 1.2% was used as the "0" level of this response surface experiment.
[0206] 4.2.2.9 Response surface optimization experiment
[0207] On the basis of single factor experiment, the formula of chewable tablets was optimized. The comprehensive score was used as the response value. The amount of dextrin added X1, magnesium stearate added X2, and aspartame added X3 were selected as three independent variable factors. The Design-Expert13 software was used to further optimize it. The Box-Behnken method was used to perform a three-factor three-level response surface analysis experiment. The experimental design and results are shown in Table 30.
[0208] Table 30 Box-Behnken test design and results
[0209]
[0210]
[0211] Design-Expert13 software was used to analyze the data in Table 31, and the coefficients of the quadratic regression equation of the three-factor three-level test were calculated. After regression fitting, significant items were selected through the results, and their significance was tested. Factors other than significant factors were removed to obtain a binary multinomial regression model for the comprehensive score on the amount of Ganoderma lucidum added, the amount of microcrystalline cellulose added, and the amount of magnesium stearate added:
[0212] Table 31 Box-Behnken test results quadratic regression variance analysis
[0213]
[0214] P<0.01, extremely significant (**); P<0.05, significant (*)
[0215] As shown in Table 31, the regression model P < 0.01 is extremely significant, which can better describe the true relationship between each factor and the response value. The model can be used to determine the tableting formula of chewable tablets. The lack of fit term P > 0.05 is not significant, indicating that the residuals are caused by random errors. Among them, the effects of the first-order terms X1 (dextrin addition), X2 (magnesium stearate addition), and X3 (aspartame addition) are all extremely significant (P < 0.01), and the effects of the second-order terms X1, X2, and X3 are also extremely significant.
[0216] The results of the F test and lack-of-fit test of the quadratic regression equation show that the model P value is less than 0.01, indicating that the model is extremely significant; the P value of the lack-of-fit term is 0.1266, which is greater than 0.05, indicating that the fit is good and this model can be used for analysis and prediction.
[0217] Corrected determination coefficient AdjR2 = 0.9996, indicating that 99.98% of the data variability can be explained by this regression model. The coefficient of variation CV% indicates the confidence of the model. The CV% of this test is 0.3953, indicating that the model equation can better reflect the more realistic test values. Therefore, the regression equation can be used to replace the real test values to analyze and predict the test results.
[0218] The three-dimensional response surface diagram expresses the strength of the interaction of each experimental factor in the form of contour lines, and the elliptical contour line shape is the most suitable. From the analysis results, it can be seen that the interaction of the addition of dextrin, magnesium stearate and aspartame has an impact on the comprehensive score of the test product Ganoderma lucidum tablets.
[0219] from Figure 1It shows that the comprehensive score of the product reaches the highest when the addition amount of dextrin is 36.20% and the addition amount of magnesium stearate is 1.6%. With the increase of the addition amount of magnesium stearate, various indicators will get better and then worse. If the amount of magnesium stearate is too large, it will deepen the softening of the tablets and weaken the hardness. At the same time, magnesium stearate itself has a dry taste, which greatly reduces the taste of Ganoderma lucidum tablets.
[0220] like Figure 2 As shown in the figure, the interaction effect between 36.20% dextrin and 0.83% aspartame is the best, and the relatively good quality of the obtained product is closely related to dextrin. The total effect of dextrin dosage on the sensory quality of Ganoderma lucidum tablets is relatively large. If dextrin is added too little, it cannot play a corresponding filling and bonding role on Ganoderma lucidum fine powder, and the compressibility of the tablets is low; if dextrin is added too much, the taste is heavy, there is discomfort in the mouth, and the acceptance is not high.
[0221] like Figure 3 As shown, when the addition amount of magnesium stearate is 3.13% and the addition amount of aspartame is 0.83%, the comprehensive effect of the obtained product is the best. However, it can be seen that aspartame, as a flavoring agent, has little effect on the quality of the Ganoderma lucidum tablets, and the influence of its addition amount on the change of the hardness and brittleness of the Ganoderma lucidum tablets is almost zero, so the 3D graph appears flat.
[0222] observe Figure 1 , Figure 2 , Figure 3 The contour plots in the table show that the interactions between the amount of dextrin added and the amount of magnesium stearate added, the amount of dextrin added and the amount of aspartame added, and the amount of magnesium stearate added and aspartame added were not significant. The variance analysis also showed that the interaction between the three situations was not significant.
[0223] It can be seen from the contour map and 3D stereogram of each response surface that the response value has an optimal value. The optimization results are as follows through the optimization program module of the software: 36.2047% dextrin addition, 3.13066% magnesium stearate addition, 0.834139% aspartame addition, and the score of the prediction model is 27.4511. Considering the feasibility of actual operation, the addition amount is corrected to 36.20% dextrin addition, 3.13% magnesium stearate addition, and 0.83% aspartame addition.
[0224] 4.2.2.10 Model Validation
[0225] Table 32 Verification results
[0226]
[0227] The experiment was repeated three times using the optimized addition amount. As shown in Table 32, the parameters of the optimal formula of Ganoderma lucidum tablets optimized by response surface methodology are accurate and reliable, with a difference of less than 5% from the test value of 27.4511. This model can be applied in practice.
[0228] The amount of Ganoderma lucidum is determined by screening the auxiliary materials. The ratio of 100% minus the auxiliary materials is the amount of Ganoderma lucidum. The goal is to add the maximum amount of Ganoderma lucidum while taking into account the proportion of Ganoderma lucidum that can be formed.
[0229] 3.5.5 Sample comparison
[0230] ZL288 was tableted according to the optimal formula and compared with five commercially available chewable tablets. The results are shown in Table 33. Figure 4 .
[0231] Table 33 Material comparison
[0232]
[0233]
[0234] By comparing the tablets of the selected materials after tabletting with five commercially available products, ZL288 is close to the commercially available samples in various indicators such as sensory score, tablet weight difference, hardness, and brittleness, indicating that the Ganoderma lucidum tablets made from ZL288 Ganoderma lucidum fruiting bodies meet the standards of commercially available products.
[0235] 3.5.6 Antioxidant test results
[0236] 3.5.6.1 Test results of DPPH free radical scavenging ability
[0237] As the concentration increases, the ability of VC to scavenge DPPH free radicals gradually increases. When the concentration is 0.12g / mL, the scavenging rate of DPPH free radicals is 99.65%. As the concentration increases, the ability of Ganoderma lucidum tablets to scavenge DPPH free radicals gradually increases. When the sample concentration is 0.10g / mL, the scavenging rate of DPPH free radicals is 89.31%, which is close to the level of VC, indicating that Ganoderma lucidum tablets have a strong scavenging ability against DPPH free radicals.
[0238] Table 34 Results of DPPH free radical scavenging ability
[0239]
[0240] 3.5.6.2 Test results of superoxide anion free radical scavenging ability
[0241] VC has a strong ability to scavenge superoxide anion free radicals. When the sample concentration is 0.04g / mL, the scavenging rate of superoxide anion free radicals is 99.80%. With the increase of concentration, the ability of Ganoderma lucidum tablets to scavenge superoxide anion free radicals gradually increases. When the sample concentration is 0.10g / mL, the scavenging rate of superoxide anion free radicals is 90.36%, which is close to the VC level. This shows that Ganoderma lucidum tablets have a strong scavenging ability for superoxide anion free radicals.
[0242] Table 35 Results of the ability to scavenge superoxide anion free radicals
[0243]
[0244] 3.5.6.3 Test results of hydroxyl radical scavenging ability
[0245] In the measured concentration range, VC always maintains a high scavenging ability for hydroxyl free radicals. When the concentration is greater than 0.1g / mL, the scavenging rate is almost close to 100%. With the increase of concentration, the scavenging ability of Lingzhi tablets for hydroxyl free radicals increases to a certain extent, but it is generally low, with the highest at 30.08%, indicating that the scavenging ability of Lingzhi tablets for hydroxyl free radicals is weak.
[0246] Table 36 Results of the ability to scavenge hydroxyl radicals
[0247]
[0248] summary
[0249] (1) The present invention uses Ganoderma lucidum as raw material, and the results of the repose angle measurement of the raw material show that the fluidity level of the selected raw material with the best mesh size is above good, which can meet the basic requirements of tableting. The filler, lubricant, and flavoring agent are screened respectively. Through literature review, market research, and experimental investigation, dextrin is selected as the filler, magnesium stearate is selected as the lubricant, and aspartame is selected as the flavoring agent.
[0250] (2) Through single-factor experiments, the three factors of dextrin addition, magnesium stearate addition, and aspartame addition were investigated. Sensory scores, tablet weight differences, hardness, and brittleness were used as evaluation indicators. The optimal dextrin addition amount was 35%, the optimal magnesium stearate addition amount was 4%, and the optimal aspartame addition amount was 1.2%.
[0251] (3) Based on the single factor, the Box-Behnken method was used to optimize the formula with dextrin addition, magnesium stearate addition, and aspartame addition as three independent variable factors and the comprehensive score as the response value. The optimal formula was 36.20% dextrin powder addition, 3.13% magnesium stearate addition, and 0.83% aspartame addition.
[0252] (4) The optimized addition amount was used for three repeated tests. The average sensory score, tablet weight difference, hardness and friability of the product were 92, 1.56%, 66.51N and 1.88%, respectively. The average comprehensive score was 27.48. Compared with the predicted value of 27.4511, the error was less than 5%, indicating that the result was not much different from the prediction. Therefore, the model has reached credibility and has corresponding utilization value. The obtained product has uniform color, smooth surface, appropriate sweet and sour taste, no bitterness, and moderate hardness.
[0253] (5) ZL288 was tableted according to the above optimal addition amount and compared with five commercially available chewable tablets for sensory evaluation, tablet weight difference, hardness, and friability. The Ganoderma lucidum tablets developed from the ZL288 sample met the commercial standards in all indicators.
[0254] (6) The antioxidant capacity of the obtained product was determined, and it was found that when the sample solution concentration was 0.10 g / ml, the scavenging rate of DPPH free radicals and superoxide anion free radicals was close to that of the control sample, indicating that the Ganoderma lucidum tablets prepared this time have a strong scavenging ability for DPPH free radicals and superoxide anion free radicals.
Claims
1. A Ganoderma lucidum, characterized in that: It is a Ganoderma lucidum deposited in the General Microbiological Center of China Microbiological Culture Collection Administration with a deposit number of CGMCC NO.40776.
2. The Ganoderma lucidum according to claim 1, characterized in that: The average radius of the Ganoderma lucidum is 77.95 cm, and the average thickness is 15.88 cm.
3. The Ganoderma lucidum according to claim 1, characterized in that: The hardness of the ganoderma lucidum is: 1133.76±64.2gf, adhesion: 0.95±0.01gf, resilience: 0.36±0.02gf, elasticity: 0.98±0.01gf, chewiness: 1060.95±70.8gf, and bitterness value is 0.88±0.
13.
4. Use of the Ganoderma lucidum according to any one of claims 1 to 3 in the preparation of health food or medicine with antioxidant function.
5. The use according to claim 4, characterized in that: The preparation of the health food or medicine is an oral preparation.
6. The use according to claim 5, characterized in that: The oral preparation is a tablet.
7. A food, characterized in that: It contains the Ganoderma lucidum described in any one of claims 1-3.
8. A ganoderma lucidum tablet, characterized in that: It contains the Ganoderma lucidum described in any one of claims 1-3.
9. The ganoderma lucidum tablet according to claim 8, characterized in that: It is prepared from the following raw materials and auxiliary materials in percentage by weight: Ganoderma lucidum 50%-80%, filler 30%-50%, lubricant 1%-5%, flavoring agent 0.6%-1.4%; the filler is one or a mixture of two or more of microcrystalline cellulose, lactose, starch, and dextrin; The lubricant is one or a mixture of two or more of magnesium stearate, talcum powder, and micro-powder silica gel; The flavor corrector is: one or a mixture of two or more of aspartame or stevioside. The ganoderma lucidum is raw powder and is sieved through a 100-200 mesh sieve.
10. The ganoderma lucidum tablet according to claim 9, characterized in that: It is prepared from the following raw materials and auxiliary materials in percentage by weight: Ganoderma lucidum 59.84%, dextrin powder 36.20%, magnesium stearate 3.13%, aspartame 0.83%; The ganoderma lucidum is raw medicinal powder and is sieved through a 120-mesh sieve.
Citation Information
Patent Citations
Lucid ganoderma tablet and preparation method thereof
CN106511403A
Ganoderma lucidum tablets and method for preparing ganoderma lucidum tablets
CN106579455A
Lentinus edodes and ganoderma polysaccharide composite tablet candy capable of improving immunity, and preparation method of lentinus edodes and ganoderma polysaccharide composite tablet candy
CN113951356A
Ganoderma lucidum coffee tea tablet candy and preparation method thereof
CN115067414A
Ganoderma lucidum tablet candy and making process thereof
CN116725110A